22 mars 1968 : une journée particulière à Nanterre. Retour sur le roman Derrière la vitre de Robert Merle - Jacques Cantier (Les Cahiers de Framespa)
The day of March 22, 1968, when a group of students occupied the administrative building of the University of Nanterre, is often considered as one of the triggers of the May 68 crisis. The evocation of this particular day, presented through the perception of a large number of protagonists, is the subject of the book Derrière la vitre by Robert Merle, an English teacher in Nanterre and novelist. Drawing on the achievements of literary studies and historiography of 68, this contribution recalls the origins of the writer's project, the analytical grid that he proposes by pointing out the topics that provoked friction within the university and French society and the reception of his work.